PEMBERIAN SAYUR PEPAYA MUDA TERHADAP KELANCARAN ASI PADA IBU NIFAS - Hotma Uli, Winda; Dwi Anjani, Arum (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
Midwifery care is a complete series of care by midwives covering the entire maternity period, from antenatal to intranatal to neonatal and postnatal including family planning contraceptive counseling. The administration of lactagogue, a substance known to help increase breast milk secretion and production, which is naturally found in papaya, is a widely adopted strategy to overcome the problem of low, or even worse, lack of breast milk production (BMP) in breastfeeding mothers. This study aims to provide comprehensive information on, from antenatal to intranatal to neonatal and postnatal by including family planning. The methods used are interviews, observations and implementation. The subject was Mrs. S who was given boiled young papaya to increase BMP during postpartum care at Hj. Hospital. Bunda Halimah Batam in 2024. The results of the examination given to Mrs. S did not show any significant problems during the antenatal and intranatal periods (which were spontaneous vaginal delivery (SVD)), the weight of the newborn was within the normal range, postpartum care to increase BMP was also reported to be no problem, and the subject decided to become a contraceptive acceptor. In conclusion, which can be done independently, during antenatal, intranatal, neonatal, postnatal, and family planning counseling, no significant problems were found. As a suggestion, midwives are encouraged to implement standardized ones starting from antenatal care to contraceptive follow-up that can help monitor and anticipate possible problems or complications early on